Política de avaliação de sistema e a gestão do resultado da prova Brasil na escola - Moreira, Rozemeiry dos Santos Marques (Universidade Federal de São Carlos, 2018)
This study thematized the construction of the theoretical and practical process of the educational evaluation regarding the use of the results in the decision making in relation to what was proposed to evaluate, considering the quality of the education system, the school and the learning. The objective was to study the general context of “Prova Brasil” in a Public School in Brazil. Ball’s studies allow for the investigation of the National Policies for System Evaluation, which is to be understood as a set of political, pedagogical, regulatory and organizational actions. This research studied the National Evaluation of School Assessment (Avaliação Nacional do Rendimento Escolar - ANERSC), also known as “Prova Brasil”. The Federal Government first started this National Evaluation through MEC/INEP in the year of 2005, with the objective of assessing the basic education in the areas of Portuguese Language and Mathematics for students from 5th to 9th grade Analyze empirically a state school in Mato Grosso do Sul to understand its micropolitics in the face of the results of Prova Brasil. In order to assess those questions, the study was structured through qualitative research, case studies, documental analysis, observation techniques, questionnaires and interviews. The interviews were conducted with 11 different subjects: Principal and assistant Principal; 3 pedagogical professionals and 6 teachers. The data was collected and analyzed in 2 perspectives: Study the process of translating policies into concrete actions; Describe the contexts of the Brazil Proof politics cycle; Recontextualize the results of Prova Brasil in the researched school. The main objective of the analysis was to identify the elements actually expressed in the macro policies and regulations and the possible influence in the micro regulation and policy of the school, effectively translating political practices and texts into practice. The results showed that the school does have its own local politics, formed through its own history in a way that is somewhat distinct from its organizational structure. The school has effectively encouraged administrators and teachers to think about their own productivity and the performance of the students. This culture and strategy has made it possible for the school to administer its work without a perfect alignment to the text of the National Policies and Regulations, specifically in relation to the actual text of “Prova Brasil” and the way its information and results are actually used.
System assessment policy and the management of the result of the Brasil test in the school
Keywords: Ciclo de políticas educacionais; Política de avaliação de sistema; Prova Brasil; Educational policies cycle; Politics of system assesment; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL